EMPOWERMENT OF YOUTH CARE FOR REPRODUCTIVE HEALTH AND IMPLEMENTATION OF GERMAS THROUGH THE TEENAGE POSYANDU IN KABAWETAN DISTRICT, KEPAHYANG REGENCY - Dino Sumaryono; Darwis Darwis; Linda Linda; Epti Yorita; Fatma Fatma (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Adolescence is a period of storm and stress, they may have various problems. The purpose of this community service is to empower adolescents to support health programs. The health promotion method is integrated with several materials to direct adolescents by providing knowledge or information they can convey health messages to the public, materials about seven Germas activities with material preparation, promoters and media in the form of posters, leaflets covering, physical exercise, the dangers of smoking, eating vegetables and fruit, environmental health and simulated latrines outreach to the community on the environment and some houses that do not have latrines and houses that have latrines but according to observations do not meet the health requirements. Number of teenagers in Sidorejo village: 64 people, boys 29 girls 35 people The number of active people coming 10 to 15 people, teenagers who smoke 12 people (41%) after implementation of quitting smoking as many as 2 people (16.6%) had high blood pressure 2 people (6.9%). The empowerment carried out has the hope that it will continue and can be applied to other villages in the form of the formation of a youth posyandu developed in all villages in order to help the government to convey health messages to adolescents in particular and the community in general for the health and prosperity of the people.Keywords : Youth Empowerment, Reproductive Health, and Implementation of GERMAS